Higher IL-9 Level is Associated with Psoriasis Vulgaris Complicated by Metabolic Syndrome - Yan L; Yu C; Zhao Z; Zhang Y; Wang R; Li C (Clinical, Cosmetic and Investigational Dermatology, 2023)
Liang Yan,1,2 Chongli Yu,1 Zhenkai Zhao,1 Yuan Zhang,1 Rui Wang,1 Chengxin Li1 1Department of Dermatology, The First Medical Center, Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China; 2Department of Dermatology, General Hospital of Central Theater Command of PLA, Wuhan, Hubei, 430070, People’s Republic of ChinaCorrespondence: Chengxin Li; Rui Wang, Department of Dermatology, The First Medical Center, Chinese PLA General Hospital, Beijing, 100853, People’s Republic of China, Tel +86-01066939315 ; Tel +86-01066939314, Email chengxinderm@163.com; wr0699@163.comPurpose: The underlying pathophysiology linking psoriasis vulgaris (PV) and metabolic syndrome (MetS) is not fully understood. The present study aimed to investigate the serum level of interleukin (IL)-9 and tissue levels of IL-9 and its receptor in PV patients with MetS and analyze the correlation of IL-9 levels with psoriasis disease severity and MetS.Methods: This study enrolled 75 PV patients with MetS, 57 PV patients without MetS, 20 healthy blood donors, and 7 healthy skin donors. Clinical, socio-demographic, and anthropometric data were obtained from all individuals. Fasting blood glucose, insulin, lipid profile levels, and serum levels of IL-9 and IL-17A were measured. The expression of IL-9 and its receptor in skin specimens in PV patients and healthy controls was determined using immunohistochemistry. Normal human epidermal keratinocytes were stimulated with five pro-inflammatory cytokines (tumor necrosis factor-α, oncostatin M, IL-22, IL-17A, and IL-1α) to establish a psoriatic keratinocyte model and subsequently treated with IL-9. Their mRNA levels of antimicrobial peptides and chemokines were measured using quantitative real-time polymerase chain reaction.Results: Serum level of IL-9 and tissue levels of IL-9 and its receptor were upregulated in PV patients with MetS. IL-9 level was positively correlated to IL-17A level; however, no significant correlation of IL-9 level with psoriasis area severity index was observed. IL-9 level had a positive correlation with the presence of MetS and its components. Correspondingly, IL-9 level positively correlated with waist circumference, body mass index, homeostasis model assessment-insulin resistance, blood pressure, and triglyceride level and negatively correlated with high-density lipoprotein cholesterol level. Additionally, IL-9 stimulated the expression of antimicrobial peptides and chemokines in a psoriatic keratinocyte model.Conclusion: Our findings confirmed that higher IL-9 level is associated with PV complicated by MetS, suggesting that IL-9 may be a link between PV and MetS.Keywords: interleukin-9, interleukin-17A, psoriasis vulgaris, metabolic syndrome